Guhong Injection Prevents Ischemic Stroke-Induced Neuro-Inflammation and Neuron Loss Through Regulation of C5ar1 - Zhang, Jingjing; Zhou, Rui; Cao, Guangzhao; Zhang, Yi; Xu, He; Yang, Hongjun (Frontiers in Pharmacology, 2022)
C5ar1 (CD88) have been identified as an important potential therapeutic target for regulating inflammation in ischemic stroke. In this study, the neuroprotective effect of Guhong injection (GHI) on middle cerebral artery occlusion (MCAO)-induced reperfusion injury was assessed and the mechanism was explored by RNA-Seq technology. GHI administered for 6 consecutive days significantly decreased body weight loss, infarction rate, neurological deficient scores and neuron loss but improved rat survival percentage, regional cerebral blood flow, after MCAO surgery. Furthermore, we identified inflammation as vital process and C5AR1 as vital target in GHI-mediated protection by using RNA-seq analysis. Further experiments confirmed that GHI decreased C5AR1, C5A, CASP3, 8-OHdG and inflammatory factors such as IL-1β, TNF, IL6, ICAM-1, MMP9 and MCP-1, and enhanced the expression of TIMP1, JAM-A and Laminin. Furthermore, GHI and its major components hydroxysafflower yellow A (HSYA), aceglutamide (AG) enhanced cell viability, reduced LDH level and C5AR1 expression in C5A-induced Neuro-2a cell damage model. In general, this study elucidated the mechanism of GHI against ischemic stroke by inhibiting inflammation and highlighted the potential important role of C5AR1 in ischemic stroke. This research provided new insights in the mechanism of GHI in resisting ischemic stroke and benefited its clinical application.